BLOQUEIO PARAVERTERBRAL TORÁCICO BILATERAL NA ANALGESIA OBSTÉTRICA RELATO DE EXPERIÊNCIA E DESCRIÇÃO DA TÉCNICA ATRAVÉS DE E BOOK - Malaguez, Adalgiso Feijó (2020)
Introduction The pain of childbirth is often the most striking in the entire life of women, who are entitled to the necessary care during labo r. In Brazil, evidence points to the low supply of pharmacological obstetric analgesia. The World Health Organization makes recommendations that indicate a de medicalization of natural childbirth, with less aggressive techniques and encourages the realizat ion of methods that provide pain relief, safely, both for the parturient and the fetus. Under this focus, the present study arose from the need to think about new or adapted techniques that are useful for increasing the offer of labor analgesia. Thoracic P aravertebral Block is a technique that can be adapted for labor analgesia, due to its potential for effectiveness and safety in the application and monitoring process. The proposal is part of the Research Priorities Agenda of the Ministry of Health: Axis 4 Development of Technologies and Innovation in Health and Axis 14 Maternal and Child Health. Objective To present a technical alternative to the neuro axis approach for local anesthetic injection to provide pharmacological analgesia Bilateral Thorac ic Paravertebral Block, through an experience report on the use of this technique successfully. Therefore, a priori, a wide literature review about the existing labor analgesia techniques was carried out and, finally, the details of the technique in an e b ook. Methodology This is an experience report that deals with the performance of a technique of obstetric analgesia to stimulate natural childbirth that would have an indication for cesarean section due to phobia of the pain of natural childbirth. The rep ort was preceded by an extensive literature review and, finally, with the description of the technique in didactic material in e book format. The project was developed during the year 2020, after approval by the Research Ethics Committee of the Franciscan University (opinion number 4,442,526). Results Bilateral paravertebral thoracic block, the chosen analgesic method, is a technique that does not use neuro axis as an anatomical substrate and does not produce hemodynamic fluctuation in the parturient and w ithout consequencesfor the fetus. The pregnant woman, after receiving analgesia, did not present pain in the first stage of labor and the use of the technique allowed, in this case, that the indication for cesarean section due to phobia of labor pain was r eviewed by the obstetric team and the childbirth developed in a natural way. In this process, the performance of the maternity nursing team was essential to conduct monitoring and care for parturient women. Final considerations This study presents a techn ical alternative with the potential to replace conventional pharmacological obstetric analgesia and contribute to pain relief in the first stage of labor. This technique can make the offer of pharmacological labor analgesia more prevalent in Brazilian mate rnity hospitals and, thus, 16 contribute to the minimization of cesarean rates nationwide, considered much higher than the percentages recommended by the World Health Organization. The benefits of this technique are also associated with its ease of use, mi nimization of complications (less possibility of sympatholysis and less hemodynamic fluctuations), the possibility of carrying it out in patients with blood dyscrasia (no contact with epidural venous plexus), lower cost for patients. health services, poten tial for replicability at the national level, as well as greater comfort for the parturient woman.